2018
DOI: 10.3390/s18041008
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Study of Fingerprint Matching Systems for Sensor Interoperability Problem

Abstract: The fingerprint is a commonly used biometric modality that is widely employed for authentication by law enforcement agencies and commercial applications. The designs of existing fingerprint matching methods are based on the hypothesis that the same sensor is used to capture fingerprints during enrollment and verification. Advances in fingerprint sensor technology have raised the question about the usability of current methods when different sensors are employed for enrollment and verification; this is a finger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…8 shows box plots of the inter-ridge distances for each dataset of the FingerPass database. The ridge spacing is in the range [5][6][7][8][9][10][11]. We argue that choosing the value of d to reflect the inter-ridge distance will improve the robustness.…”
Section: ) An Analysis Of the Effect Of The Co-ror Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…8 shows box plots of the inter-ridge distances for each dataset of the FingerPass database. The ridge spacing is in the range [5][6][7][8][9][10][11]. We argue that choosing the value of d to reflect the inter-ridge distance will improve the robustness.…”
Section: ) An Analysis Of the Effect Of The Co-ror Parametersmentioning
confidence: 99%
“…Recent research demonstrated the significance of studying the effect of using different fingerprint sensors on automatic fingerprint-matching [5]. Jain and Ross [1] proved that the performance of a matching system decreases drastically when fingerprints are captured with two different sensors.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, all these biometric recognition methods must work in an interoperable and ubiquitous way in a highly connected world. Over the years, several studies have tackled the problem of interoperability in fingerprint sensors [13,34,35], evidencing several challenges. Another challenge encountered occurs when matching databases from different countries or regions that use different standards.…”
Section: Multiresolution Synthetic Fingerprint Generationmentioning
confidence: 99%
“…Usually, the above fingerprints do not contain enough details, and it is difficult for the conventional matching methods based on the details to achieve ideal results. Although most electronic consumer terminals cannot provide enough computing power for AI-based image matching algorithms, (1)(2)(3)(4)(5)(6) image matching based on local feature points is widely used in the above scenes, such as the well-known scale-invariant feature transform (SIFT) algorithm, (7) the speeded-up robust features (SURF) algorithm, (8) binary robust independent elementary features (BRIEF) algorithm, (9) and the features from accelerated segment test (FAST) and rotated BRIEF (ORB) algorithm. (10) However, differences between the various image matching algorithms based on feature points, such as orientation, coordinates, and sub-vector description, may lead to diverse effects on the same image.…”
Section: Introductionmentioning
confidence: 99%